Synthesis and Characterization of Hierarchical Structured TiO2 Nanotubes and Their Photocatalytic Performance on Methyl Orange. (19th March 2015) - Liu, Kai; Lin, Shiwei; Liao, Jianjun; Pan, Nengqian; Zeng, Min
Abstract : Hierarchical structured TiO2 nanotubes were prepared by mechanical ball milling of highly ordered TiO2 nanotube arrays grown by electrochemical anodization of titanium foil. Scanning electron microscopy, transmission electron microscopy, X-ray diffraction, specific surface area analysis, UV-visible absorption spectroscopy, photocurrent measurement, photoluminescence spectra, electrochemical impedance spectra, and photocatalytic degradation test were applied to characterize the nanocomposites. Surface area increased as the milling time extended. After 5 h ball milling, TiO2 hierarchical nanotubes exhibited a corn-like shape and exhibited enhanced photoelectrochemical activity in comparison to commercial P25. The superior photocatalytic activity is suggested to be due to the combined advantages of high surface area of nanoparticles and rapid electron transfer as well as collection of the nanotubes in the hierarchical structure. The hierarchical structured TiO2 nanotubes could be applied into flexible applications on solar cells, sensors, and other photoelectrochemical devices.